Experimental study on combined defrosting performance of heat pump air conditioning system for pure electric vehicle in low temperature - Zhou, Guanghui; Li, Haijun; Liu, Enhai; Li, Bo; Yan, Yuying; Chen, Tong; Chen, Xiaonan (Elsevier, 2017)
The development of defrosting technology is a crucial technical barrier to the application of the heat pump air conditioning system for the pure electric vehicle. The frosting on the air conditioning system significantly affects systematic performance and reliable operation especially in low temperature and high humidity climate condition. Therefore, in this paper, an experimental study of low-temperature heat pump air conditioning system with the combined defrost technology of increasing enthalpy and temperature is carried out to find proper thermal management solutions. Based on the reverse-cycle methods, the combined defrost technology makes full use of the compressor air-supplying enthalpy-adding, air-cooled heat exchanger inside the vehicle preheating, temperature-raising, enthalpy-adding and the external heat exchanger condensation temperature-increasing technologies. The fast defrosting process can be realized by means of releasing the condensation heat and volume significantly while the outer heat exchanger is conducting a defrosting operation. Meanwhile, the cold cabin sensitivity can be reduced while defrosting process taking place correspondingly. Experimental results show that under the operating condition of −20 °C outside environment temperature and 80% relative humidity, instant defrosting time at fully defrosted air-cooled heat exchanger outside the vehicle can be controlled within 100 s.